DISTRIBUTION OF BLUE CARBON ECOSYSTEMS IN SMALL ISLANDS USING LANDSAT-8 (CASE STUDY IN PRAMUKA ISLAND) - Hanjaniputri, Budi Utami (Jurnal Pendidikan Geografi Gea, 2017)
The ecosystem of the seashore and the ocean consist of mangrove, seagrass beds, and brackish mars which can pervade the carbon dioxide from the atmosphere and the ocean in the bigger amount than the forest does. That kind of ecosystem known as the Blue Carbon Ecosystem. Ecosystem service mapping is the most important step in the valuation, because it shows important information about ecosystem service of certain area in the bigger scale. This research is aimed to map the ecosystem of mangrove and seagrass beds which exist in small island. This blue carbon ecosystem mapping used remote sensing technology by using satellite imagery Landsat-8. Normalized difference vegetation Index (NDVI) method used to map the ecosystem of mangrove. While, to map the seagrass beds ecosystem used unattended clarification method after going through the correction of water column of Depth-Invariant Index (DII). The final result shows that Pramuka Island has mangrove ecosystem wider than two Islands around it., while the widest seagrass ecosystem is in Panggang Island. It happens because the ecosystem of mangrove in the research location is the result of mangrove planting activity, and it is different with the ecosystem of seagrass which grew naturally. Mangrove planting activity is more focused to Pramuka Island.